Respostas

A melhor resposta!
  • Usuário do Brainly
2014-08-31T14:59:09-03:00
Olá, Júlia !

4^{x+1}-33\cdot2^{x}+8=0

Observe que:

4^{x+1}=(2^2)^{x+1}=2^{2x+2}

Assim:

2^{2x+2}-33\cdot2^{x}+8=0

Mas, 2^{x}\cdot2^{x}\cdot2^2=4\cdot(2^{x)^2

4\cdot(2^{x})^2-33\cdot2^{x}+8=0

Seja 2^{x}=k, então:

4k^2-33k+8=0

\Delta=(-33)^2-4\cdot4\cdot8=1~089-128=961

k=\dfrac{-(-33)\pm\sqrt{961}}{2\cdot4}=\dfrac{33\pm31}{8}.

k'=\dfrac{33+31}{8}=\dfrac{64}{8}=8

k"=\dfrac{33-31}{8}=\dfrac{2}{8}=\dfrac{1}{4}

Deste modo, 2^{x}=8\Rightarrow\boxed{x=3} ou 2^{x}=\dfrac{1}{4}\Rightarrow\boxed{x=-2}.
2 5 2